The impact of repeated reading intervention on reading self-efficacy and fear of negative evaluation in Arabic-speaking students - ALhuraybi, Fatimah Ali; Al-Osail, Abdulaziz Faleh; Hafez, Waheed Elsayed; Ibrahim, Ashraf Ragab; Abdelrahman, Faiza Ahmed; Abdelrahman, Eman Ahmed; Abdellatif, Mohamed Sayed; Nemt-allah, Mohamed Ali (Research Journal in Advanced Humanities, 2026)
This randomized controlled trial examined the effectiveness of repeated reading intervention on reading self-efficacy and fear of negative evaluation (FNE) among Arabic-speaking preparatory students. Sixty second-grade students (ages 14-15) from two preparatory institutes in Gharbia Governorate, Egypt, were randomly assigned to experimental (n=30) or control (n=30) groups. The experimental group received an eight-week repeated reading intervention with three 45-minute sessions per week, incorporating fluent reader modeling, performance-based feedback, and small-group tutoring formats specifically adapted for Arabic orthographic challenges. The control group continued standard Arabic reading instruction. Measurements were collected at pre-intervention, post-intervention, and four-week follow-up using validated scales for reading self-efficacy and FNE. Repeated measures ANOVA revealed significant time × group interactions for both outcomes. The experimental group demonstrated substantial improvements in reading self-efficacy (η²p = 0.44, large effect) and significant reductions in FNE (η²p = 0.16, medium effect), with gains maintained at follow-up. Control group scores remained stable across all time points. These findings provide the first evidence that repeated reading interventions can simultaneously enhance reading self-efficacy and reduce FNE in Arabic-speaking students, suggesting that such interventions address both cognitive and psychological dimensions of reading difficulties with sustained benefits.